The Role of Institutional Repositories in Facilitating Scholarly Communication at the Open University of Tanzania and University of Dar es Salaam - Gideon, Hetty; Samzugi , Athumani S. (University of Dar es Salaam Library Journal, 2024)
This study explored the role of Institutional Repositories (IR) in facilitating scholarly communication in Institutions of higher learning in Tanzania with the case of the Open University of Tanzania and the University of Dar es Salaam. The study examined the benefits of IR among researchers and explored the challenges facing its management. The study employed a survey research design. Data was collected using a questionnaire survey, involving 148 postgraduate students. Moreover, the study used interviews to collect data from two library directors and two directors of research and publications of the two Institutions of higher learning under review. Of the respondents, 89(73.6%) reported that IR enhances research outputs. However, they also identified several challenges including poor internet connectivity 56(83.6%), unreliable power supply 49(73.1%) and limitations of accessing IR contents 34(50.7%). Other bottlenecks identified included a lack of policy to guide the IR management, limited motivation among academic staff to submit their research output, and a lack of institutional support and commitment from the management. Based on the findings, strategies suggested include formulating and instituting comprehensive policies to guide the proper management of IR, enhanced management support in allocating sufficient budget for ICT infrastructures and hardware, and motivating staff to use IR. In addition, the librarians should market the services provided by IR to inform users on what is available in the IRs, because the value of information deposited depends much on its accessibility and usage. Doing so could further effectively contribute to enhancing scholarly communication at the two institutions.